Development of an expert consensus checklist for emergency ultrasound. Issue 4 (3rd August 2022) - Bailitz, John; O'Brien, James; McCauley, Matt; Murray, David; Jung, Christine; Peksa, Gary; Gottlieb, Michael
Abstract: Background: Within today's competency‐based medical education, traditional set number proficiency benchmarks have been called into question. Checklists may help guide individualized training and standardized outcomes. However, multicenter expert consensus checklists based on established guidelines with supporting validity evidence have not been published for specific emergency ultrasound (EUS) applications. We describe a robust national EUS expert consensus methodology for developing a checklist for the extended focused assessment with sonography in trauma (eFAST examination). Methods: Utilizing the ACEP imaging compendium as a primary reference, 10 national EUS experts iteratively refined and agreed upon a final checklist. To obtain initial reliability and validity evidence, two different EUS experts blinded to resident experience then assessed 24 residents performing an eFAST in a simulated environment. Inter‐rater reliability of the checklist was assessed using Cohen's kappa coefficient. Validity was assessed by comparing mean performance with the Student's t‐test and discriminant ability of individual checklist items using item‐total correlation. Results: The 10 EUS experts agreed on the final checklist items after two rounds of iterations. When evaluating 24 emergency medicine (EM) PGY‐1 to ‐4 residents, the kappa correlation between two blinded EUS faculty raters was moderate at 0.670. Kappa and agreement were near‐perfect or perfect in right and left chest image optimization, right upper quadrant (RUQ) probe placement, RUQ anatomy identification, and pelvic first‐view anatomy identification. The difference in checklist performance between junior and senior EM residents was significant at −8.1% (p = 0.004). Identification of pelvic structures and placement of the probe for pelvic views were found to have an excellent item‐total correlation with values of >0.4. Conclusions: We have described a robust national EUS expert consensus methodology for developing an eFAST checklist based on the ACEP imaging guidelines. Based on this encouraging initial reliability and validity evidence, further research and checklist development is warranted for additional EUS applications.